(untitled) (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2025)
The enactment of Law Number 6 of 2023 concerning the Ratification of Government Regulation in Lieu of Law Number 2 of 2022 on Job Creation into Law requires that any permanent utilization of marine space must have basic permit for marine spatial utilization activities (KKPRL). The process of granting KKPRL permit is carried out by assessing the conformity of activities with the guidelines for zoning water space utilization based on the Regional Spatial Plan issued by the Provincial Government. The lack of information regarding the guidelines for marine space utilization causes applicants for marine space utilization activities to be unaware of the guidelines that can be applied to the location, thus hindering the process of issuing the KKPRL permit. The research aims to design a digitalization system for providing spatial utilization guidelines documents in the work area of BPSPL Makassar, which can be accessed online by marine space utilization stakeholders. This will facilitate checking the conformity of marine space utilization activities and accelerate the process of issuing the KKPRL permit. As an initial step, a digitalization system for marine spatial utilization guidelines was designed for two provinces in the work area of BPSPL Makassar, which have integrated the marine spatial planning and land spatial planning into Regional Spatial Plan (RTRWP), namely South Sulawesi Province and Central Sulawesi Province. This initial design will continue to be developed in line with the availability of RTRWP integration documents in four other provinces within the work area of BPSPL Makassar. Keywords: digitalized, guidelines, spatial, webgis